Tupistra chinensis a traditional Chinese plant suppresses tumor growth and metastasis in vitro against ER positive and triple negative breast cancer - Adyasa Samantaray; Debasish Pradhan (Elsevier, 2024)
Aim: To investigate the effects of Tupichinol E, an alkaloid present in Tupistra chinensis BAKER (Liliaceae), on the metastasis of triple-negative mammary carcinoma in vitro and elucidate the underlying mechanisms. Tupichinol E binding to EGFR stabilizes the protein structure and is a pharmacologically active substance that can be used against cancer due to its potent activity. Methods: The growth of MCF-7 and MDA-MB-231 cells was assessed using the MTT assay. The apoptosis and cell cycle of MCF-7 cells were evaluated with flow cytometry, and the related proteins were examined using Western blotting. Results: Tupichinol E (50-200 μmol/L) inhibits the growth of MCF-7 cells in a dose- and time-dependent manner (the IC50 values are 85.05 ± 1.08 and 50.52 ± 1.06 μmol/L, respectively, at 48 and 72 h). Treatment of MCF-7 cells with Tupichinol E (50-200 μmol/L) dose-dependently induced apoptosis of MCF-7 cells, accompanying the activation of caspase 3. The cells treated with Tupichinol E (100 and 200 μmol/L) significantly increased the percentage of cells in the G2/M phase with a reduction in the expression of cyclin B1. Conclusion: These results demonstrated that Tupichinol E is an effective anti-tumor compound in vitro and has the potential to be developed as a new anticancer drug.